SOCIAL MEDIA AS A PLATFORM OF PERFORMING ARTS EDUCATION DURING COVID-19 PANDEMIC - Afrizal Yudha Setiawan; Dwiyana Habsary; Indra Bulan (JPKS (Jurnal Pendidikan dan Kajian Seni), 2021)
This article aims to describe the use of social media as a platform for performing arts education. The main problem in this research is social distancing due to the Covid-19 pandemic, which causes performing arts activities must be presented without audiences (online performing arts). Social media is an alternative media for art creator (artists/ choreographer/ musician) to present their work and deliver the messages to the audience. The question in this research is whether the social media can replace the role of performing arts to deliver the messages from the creator to the audience. This study used qualitative research methods. The objects involved in this study were videos of performing arts on social media. Data was collected thorugh documentation, and literature review. The results of the study describe about the communication form between performing arts elements (creator and audiences) of the show presented on social media.